Industrial Marketing Strategy For E.B. Copper Sdn .Bhd - Teong, Quah Chee (2000)
The purpose of this report is to study the industrial marketing strategies of E.B. Copper, a Malaysia manufacturing company. E.B. Copper was used as a case study because only limited companies are available in this copper bend industry and further not manay research being studied on Malaysia's company.